A dimensão afetiva na interação plurilingue: Dinâmicas de negociação de imagens e estereótipos na interação romanófona em chat - Sílvia Melo-Pfeifer; Maria Helena Araújo e Sá (Universidade do Minho, 2017)
Given the importance of the Internet as a contact tool at an intercultural and multilingual level, and considering a definition of communication spaces as places where images about the Other emerge and are negotiated, we will analyze a corpus of plurilingual interactions in chat conversations (in Romance Languages), in order to study the dynamics of the images and stereotypes in this communication situation. We will attempt to uncover barriers to intercultural communication, expose some utopias about it (like the use of a lingua franca as a solution to communication problems) and discover the possibilities propelling interaction, such as an affective relationship with the languages, the speakers and the communication situation. Data discussion will allow us to demonstrate how crossed images and stereotypes of the speakers towards others, their languages and cultures emerge in the interaction, how they feed and stimulate conversation and how they trigger 'happy' moments of plurilingual communication.